Sclerosing angiomatoid nodular transformation of spleen masquerading as carcinoma breast metastasis: Importance of splenic biopsy in obviating splenectomy - Deep Dutta; Meha Sharma; Vrushali Mahajan; Prem Chopra (Wolters Kluwer Medknow Publications, 2016)
Metastasis to spleen is rare and usually occurs in the setting of extensive multivisceral metastatic disease. A 60-year-old lady with appropriately managed early breast cancer (breast conservative surgery for Grade-2 infiltrative ductal carcinoma [0.7 cm × 0.5 cm diameter]) in 2006, was detected to have splenic incidentaloma (1.4 cm × 0.8 cm) in November 2012, which was fluoro-deoxy-glucose (FDG) avid on positron emission tomography. Fine needle spiration cytology (FNAC) was normal. More than doubling of lesion size by March 2015 (3.83 cm × 3.03 cm diameter) with persistent FDG positivity lead to Tru-Cut biopsy of spleen, which revealed multiple nodular areas of congestion and hemorrhage, composed of sinusoids (CD31+, CD8+, and CD34−), capillaries (CD31+, CD8−, and CD34+), and small veins (CD31+, CD8−, and CD34−), fibrosis, around these nodular areas along with numerous histiocytes (CD68+) consistent with diagnosis of sclerosing angiomatoid nodular transformation (SANT) of spleen. SANT is a benign, reactive vascular transformation of spleen, notorious to mimic metastasis, the cause of its 18FDG avidity due to its rich content of macrophages and myofibroblasts, usually diagnosed postsplenectomy. This report highlights the importance of splenic biopsy over FNAC is diagnosing splenic incidentalomas, which can help prevent splenectomy, and hence the associated morbidity. This is the first report of SANT in carcinoma breast mimicking metastasis.